Preparation method of hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating

A hydroxyl-modified graphene oxide synergistic phosphate coating addresses aggregation issues and degradation by forming a stable passivation film and providing cathodic protection, significantly improving corrosion resistance in epoxy resin systems.

CN118374203BActive Publication Date: 2024-12-24ANHUI BONA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410612175.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2024-12-24
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

Graphene oxide aggregates in polymer matrices due to van der Waals forces, limiting its effectiveness as an anti-corrosion enhancer, while zinc phosphate-based coatings face degradation and efficiency issues, hindering their practical application in corrosion protection.

Method used

A method to prepare a hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating by dispersing graphene oxide in water, adding zinc acetate and ammonium phosphite, forming a GO-HAP nanocomposite, and incorporating it into an epoxy resin with a curing agent to create a tightly structured coating.

Benefits of technology

The coating effectively inhibits corrosion by blocking ion penetration, forming a stable passivation film, and providing cathodic protection, enhancing the corrosion resistance of epoxy resin systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004843971900000091
    Figure BDA0004843971900000091
  • Figure BDA0004843971900000101
    Figure BDA0004843971900000101
Patent Text Reader

Abstract

The invention discloses a method for preparing a hydroxyl-modified graphene oxide collaborative phosphate anti-rust coating, wherein the hydroxyl-modified graphene oxide collaborative phosphate anti-rust coating is prepared by hydroxyl-modified graphene oxide, zinc acetate and phosphite. Specifically, the following steps are included: S1: Preparation of hydroxyl-modified graphene oxide: dissolving graphene oxide in deionized water, first adding calcium chloride, and then adding disodium ethylenediaminetetraacetic acid to prepare solution A; dissolving disodium ethylenediaminetetraacetic acid in disodium hydrogen phosphate solution to prepare solution B; adding solution B to solution A and adding anhydrous ethylenediamine to adjust the pH to 7-9, stirring, aging and washing to obtain the hydroxyl-modified graphene oxide. The corrosion-inhibiting phosphate anti-rust pigment prepared by the method of the invention has good anti-rust effect, long action time, and high social use value and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of rust-proof pigment preparation, and in particular to a method for preparing a hydroxyl-modified graphene oxide synergistic phosphate rust-proof coating. Background Art

[0002] In 2004, Geim and Novoselov first isolated a single layer of carbon atoms, graphene, from graphite. Graphene has attracted widespread attention due to its unique mechanical, electrical, thermal, and physicochemical properties. However, its inherent chemical stability and hydrophobicity make it difficult to disperse and apply in coatings.

[0003] Graphene oxide is an important derivative of graphene. Due to the presence of functional groups such as carboxyl, hydroxyl, and epoxy groups on its surface, graphene oxide is more easily covalently or non-covalently functionalized. This can improve the compatibility of graphene oxide with polymers. In addition, graphene oxide has excellent properties such as high aspect ratio, high specific surface area, and impermeability to external corrosive media, making it easy to apply in the field of corrosion protection. It has been reported that graphene oxide has been added to polymers as an anti-corrosion enhancer to improve corrosion resistance. However, due to the presence of van der Waals forces between flaky nanofillers, graphene oxide easily aggregates in the polymer matrix, making it difficult to achieve the expected corrosion resistance.

[0004] Zinc phosphate is a versatile material with diverse morphologies and crystal structures, and is used in a wide range of fields. In the field of corrosion protection, zinc phosphate pigments are a safe alternative to lead- and chromate-based anticorrosive pigments. The passivation effect of zinc phosphate creates a passivation layer on the steel surface, forming a modified iron oxide coating with excellent adhesion. It also produces mixed oxides of phosphorus and iron, both of which have anticorrosive properties. The presence of phosphorus compounds can also enhance the polarization resistance of the steel surface, reduce the critical current density required for passivation, and enhance the stability of the passivation film. Especially in the presence of chlorides, it can improve the corrosion resistance of the substrate, achieving an anticorrosive effect comparable to that of chromate anticorrosive pigments. However, the difficulty of degradation and low efficiency of corrosion inhibitors still limit their practical application. Summary of the Invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating. The anti-rust coating is prepared by the method of the present invention, and the prepared anti-rust pigment has good and stable anti-rust effect.

[0006] The technical solution of the present invention is achieved as follows:

[0007] The present invention provides a method for preparing a hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating, which specifically comprises the following steps:

[0008] S1: Preparation of hydroxyl-modified graphene oxide

[0009] Dissolving graphene oxide in deionized water, first adding calcium chloride at a mass ratio of 20-100, and then adding disodium ethylenediaminetetraacetate at a mass ratio of 0.5-2 to calcium chloride to prepare solution A; dissolving an equal amount of disodium ethylenediaminetetraacetate in disodium hydrogen phosphate solution to prepare solution B; adding solution B to solution A and adding anhydrous ethylenediamine to adjust the pH to 7-9, stirring, aging, and washing to obtain the hydroxyl-modified graphene oxide;

[0010] S2: Preparation of hydroxyl-modified graphene oxide synergistic phosphate composites

[0011] Dispersing the hydroxyl-modified graphene oxide described in S1 in deionized water to prepare a hydroxyl-modified graphene oxide dispersion, then sequentially adding zinc acetate and ammonium phosphite solution in a molar ratio of 1:1-1:3 to the hydroxyl-modified graphene oxide dispersion, and obtaining the hydroxyl-modified graphene oxide synergistic phosphate composite material after purification;

[0012] S3: Preparation of hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating

[0013] The hydroxyl-modified graphene oxide synergistic phosphate composite material described in S2 is dispersed in deionized water to prepare a dispersion, and then the dispersion is added to the epoxy resin. After stirring, a curing agent is added and the mixture is dried to obtain the hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating.

[0014] Furthermore, the conditions for adding solution B to solution A in step S1 are: stirring rapidly at 40-60°C at a rate of 1.5-2.5 ml·min -1 Speed ​​dropwise.

[0015] Furthermore, after the reaction in step S2 is completed, ammonia water is added dropwise to adjust the pH value to 7-9.

[0016] Furthermore, the dispersion is added in the following manner: adding the dispersion into the epoxy resin at a stirring speed of 500-700 r / min and stirring for 4-6 hours.

[0017] Furthermore, in step S3, the mass ratio of the graphene oxide synergistic phosphate composite material to the epoxy resin is 1:100-1:20.

[0018] Furthermore, the curing agent in step S3 is an aromatic amine curing agent, preferably one or more of m-phenylenediamine, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenyl sulfone, m-aminomethylamine, and benzidine.

[0019] The beneficial effects of adopting the above scheme are:

[0020] Graphene oxide has outstanding properties such as high electron mobility, large specific surface area, good electrical properties, and strong mechanical properties, which has attracted people's attention. The layered structure of graphene oxide is a good barrier to corrosive ions, oxygen and water. The presence of surface grafted functional groups (carboxyl, hydroxyl, epoxy, etc.) promotes the combination of graphene oxide flakes and epoxy resin systems. More importantly, the electron collection ability of graphene oxide flakes can inhibit the transfer of electrons during the entire corrosion reaction process. Despite this, the acidity generated by the carboxyl groups on the graphene oxide flakes will still affect the effect of protecting the metal substrate after long-term immersion. Modifying graphene oxide with hydroxyl groups is beneficial to neutralize the acidity and achieve long-term anti-corrosion performance.

[0021] Ca 2+ The ions first bind to graphene oxide and then grow in situ on the graphene oxide flakes to form a graphene oxide-hydroxyapatite (GO-HAP) nanocomposite. The complex interlaced structure of the GO-HAP nanocomposite effectively blocks the penetration of corrosive substances. The abundant hydroxyl groups in HAP replace the free Cl- ions in the coating, forming a more stable chloroapatite, which reduces metal damage. In the presence of graphene oxide, the corrosion reaction is further suppressed by hindering the cathodic half-reaction. Therefore, the synergistic and complementary protective effects of the GO-HAP nanocomposite can significantly improve the corrosion resistance of epoxy resin systems.

[0022] Furthermore, the graphene oxide substrate played an adhesive role in enhancing the coupling between the oxidized GO-HAP nanocomposite and the epoxy resin, resulting in a tightly structured anti-corrosion coating. Therefore, the addition of GO-HAP nanocomposite as an anti-corrosion pigment to the epoxy resin system can effectively improve the shielding performance of the system.

[0023] The P in phosphite is +3, which is both oxidizing and reducing. Under alkaline conditions, the iron substrate loses electrons to form trace ferrous ions, which react with P03 3- Oxidation-reduction reaction occurs to form a metal oxide passivation film γ-Fe2O3, thereby showing the flash rust inhibition effect. At the same time, P03 3- It also has partial reducing properties. During the drying process of the paint film, it reacts with a small amount of oxygen dissolved in the paint to produce P04 3- , consumes part of the dissolved oxygen, and also plays a certain auxiliary role in inhibiting flash rust.

[0024] P04 generated at the same time 3- Synergistic Zn 2+It reacts with the metal surface to form a dense metal oxide film - Zn-P2O5 phosphating film coating. At this time, a passivation reaction occurs on the metal surface. The molecular formula of the passivation product is the iron-containing phosphating passivation film ZnFe(PO4)2·4H2O. This passivation film has a certain adhesion and is tightly attached to the metal surface, thus having high corrosion resistance. At the same time, zinc phosphate is a compound with crystal water. In corrosive media, it can dissociate with its crystal water to form a basic salt with the molecular formula Zn3(PO4)2(OH)n·(4-n)H2O. This type of basic salt can form a layer of heteropolyacid complex on the surface of the metal material, which can achieve a certain anti-rust effect.

[0025] At the same time, anti-rust pigments can also provide cathodic protection, because Zn 2+ The electrode potential of the metal is more negative than that of steel, so in the process of corrosion, the first thing to be corroded will be the anti-corrosion coating on the surface, which continuously gains electrons on the surface of the metal substrate, thereby protecting the inside of the substrate from corrosion.

[0026] Zinc phosphite particles are fixed to the graphene oxide surface, with a certain gap between adjacent zinc phosphite particles, reducing particle agglomeration and providing additional diffusion space for passivating ions. At the same time, the hydroxyl-modified graphene oxide synergistic phosphate composite has a large surface area, further improving the release rate of passivating ions.

[0027] Since epoxy coatings inevitably produce micropores during the curing process, these micropores accelerate the invasion of external corrosive media and reduce the protective effect of the coating on the metal. For hydroxy graphene oxide synergistic phosphate anti-rust coatings, since both zinc phosphate and graphene oxide have a flaky structure, this has a certain inhibitory effect on the penetration of corrosive media, thereby improving the protective effect of the epoxy coating. The phosphate anti-rust coating containing hydroxy graphene oxide synergistic phosphate has a maze effect in the early stage of immersion, extending the penetration path of external corrosive media. Compared with the prior art: The beneficial effects of the present invention are:

[0028] 1. Under alkaline conditions, the iron substrate loses electrons to form trace ferrous ions, which react with P03 3- Oxidation-reduction reaction occurs to form a metal oxide passivation film γ-Fe2O3, thereby showing the flash rust inhibition effect. At the same time, P03 3- It also has partial reducing properties. During the drying process of the paint film, it reacts with a small amount of oxygen dissolved in the paint to produce P04 3- , consumes part of the dissolved oxygen, and also plays a certain auxiliary role in inhibiting flash rust.

[0029] 2. The complex interlaced structure of the GO-HAP nanocomposite effectively blocks the penetration of corrosive substances. The abundant hydroxyl groups in HAP replace free Cl- ions in the coating, forming a more stable chloroapatite and reducing metal damage. In the presence of graphene oxide, corrosion is further suppressed by hindering the cathodic half-reaction. Therefore, the synergistic and complementary protective effects of the GO-HAP nanocomposite can significantly improve the corrosion resistance of epoxy resin systems.

[0030] 3. The graphene oxide substrate plays an adhesive role in enhancing the coupling between the oxidized GO-HAP nanocomposite and the epoxy resin, resulting in a tightly structured anti-corrosion coating. Therefore, the GO-HAP nanocomposite, as an anti-corrosion pigment, can effectively improve the shielding performance of the epoxy resin system. DETAILED DESCRIPTION

[0031] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0032] Reagent Description:

[0033] Graphene oxide, calcium chloride, disodium edetate, disodium hydrogen phosphate, zinc acetate, ammonium phosphite, epoxy resin, and diaminodiphenyl sulfone were all analytically pure and were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0034] Example 1

[0035] This embodiment provides a method for preparing a graphene oxide-synergistic phosphate anti-rust coating, which specifically includes the following steps:

[0036] S1: Preparation of hydroxyl-modified graphene oxide

[0037] 0.06 g of graphene oxide was dissolved in 100 mL of deionized water, 2.27 g of calcium chloride was added first, and then 0.1 g of disodium ethylenediaminetetraacetate was added to prepare solution A; 0.1 g of disodium ethylenediaminetetraacetate was dissolved in 100 mL of 0.15 mol·L -1 Prepare solution B with sodium hydrogen phosphate solution; add solution B at 2 ml·mol -1 The mixture was added to solution A at a rate of 100 μg / min and anhydrous ethylenediamine was added to adjust the pH to 8. After stirring for 20 min, the mixture was aged at room temperature for 12 h and washed with deionized water to obtain the hydroxyl-modified graphene oxide.

[0038] S2: Preparation of hydroxyl-modified graphene oxide synergistic phosphate composites

[0039] Take 50 mg of the hydroxyl-modified graphene oxide and disperse it in 50 mL of deionized water to obtain a uniformly dispersed graphene oxide dispersion. -1 The zinc acetate solution was slowly added to the graphene oxide dispersion and stirred for 5 h. -1 The ammonium phosphite solution is added dropwise to the mixed solution, and ammonia water is added dropwise to adjust the pH value to 8. After filtering, washing, and drying, the hydroxyl-modified graphene oxide synergistic phosphate composite material is obtained;

[0040] S3: Preparation of hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating

[0041] 0.6 g of the hydroxyl-modified graphene oxide synergistic phosphate composite material was dissolved in 10 mL of deionized water to prepare a dispersion. The dispersion was then added to 60 g of a water-based epoxy resin at 600 r / min and stirred for 5 hours. Then, 5.4 g of diaminodiphenyl sulfone was added and stirred for another 5 minutes to obtain the graphene oxide synergistic phosphate antirust coating. The coating was dried at room temperature for 24 hours and then transferred to a 50°C oven for drying for 168 hours to obtain the hydroxyl-modified graphene oxide synergistic phosphate antirust coating film.

[0042] Salt spray resistance test: Then prepare the steel plate paint film sample according to GB / T1765-1989, conduct the normal temperature salt water resistance test according to GB-1763-79 and evaluate the rust condition after 192 hours.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the amount of the hydroxyl-modified graphene oxide synergistic phosphate composite material added in step S3 is 1.2 g.

[0045] The other parts are exactly the same as in Example 1.

[0046] Example 3

[0047] The difference between this embodiment and embodiment 1 is that the amount of the hydroxyl-modified graphene oxide synergistic phosphate composite material added in step S3 is 1.8 g.

[0048] The other parts are exactly the same as in Example 1.

[0049] Example 4

[0050] The difference between this embodiment and embodiment 1 is that the amount of the hydroxyl-modified graphene oxide synergistic phosphate composite material added in step S3 is 2.4 g.

[0051] The other parts are exactly the same as in Example 1.

[0052] Example 5

[0053] The difference between this embodiment and embodiment 1 is that the amount of the hydroxyl-modified graphene oxide synergistic phosphate composite material added in step S3 is 3.0 g.

[0054] The other parts are exactly the same as in Example 1.

[0055] Example 6

[0056] The difference between this embodiment and embodiment 1 is that the amount of ammonium phosphite solution added in step S2 is 3 mL.

[0057] The other parts are exactly the same as in Example 1.

[0058] Example 7

[0059] The difference between this embodiment and embodiment 1 is that the amount of ammonium phosphite solution added in step S2 is 9 mL.

[0060] The other parts are exactly the same as in Example 1.

[0061] Comparative Example 1

[0062] The difference between this embodiment and embodiment 1 is that the amount of hydroxyl-modified graphene oxide added to the dispersion in step S2 is 0.

[0063] The other parts are exactly the same as in Example 1.

[0064] Tests and results

[0065] The results are shown in Table 1.

[0066] Table 1

[0067]

[0068]

[0069] As shown in Table 1, the corrosion-inhibiting phosphate antirust pigment prepared by the method of the present invention has good antirust effect, long action time and the most significant antirust effect.

[0070] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing a hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating, characterized in that: The specific steps include: S1: Preparation of hydroxyl-modified graphene oxide Graphene oxide was dissolved in deionized water, and calcium chloride was first added, followed by disodium ethylenediaminetetraacetate to prepare solution A; Disodium ethylenediaminetetraacetate is dissolved in disodium hydrogen phosphate solution to prepare solution B; Solution B is added to solution A and anhydrous ethylenediamine is added to adjust the pH to 7-9, and the mixture is stirred, aged and washed to obtain the hydroxyl-modified graphene oxide; S2: Preparation of hydroxyl-modified graphene oxide synergistic phosphate composites Dispersing the hydroxyl-modified graphene oxide described in S1 in deionized water to prepare a hydroxyl-modified graphene oxide dispersion, then sequentially adding zinc acetate and ammonium phosphite solution to the hydroxyl-modified graphene oxide dispersion, and obtaining the hydroxyl-modified graphene oxide synergistic phosphate composite material after purification; S3: Preparation of hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating The hydroxyl-modified graphene oxide synergistic phosphate composite material described in S2 is dispersed in deionized water to prepare a dispersion, and then the dispersion is added to an epoxy resin, and a curing agent is added after stirring and the mixture is dried to obtain the hydroxyl-modified graphene oxide synergistic phosphate anti-rust coating; The mass ratio of graphene oxide to calcium chloride in step S1 is 100:1-20:1; The mass ratio of disodium ethylenediaminetetraacetate to calcium chloride in solution A in step S1 is 0.5:1-2:1; The amount of disodium edetate used in solution A and solution B in step S1 is the same; The conditions for adding solution B to solution A in step S1 are: stirring rapidly at 40-60°C at a rate of 1.5-2.5 mL·min -1 Speed ​​dripping; The molar ratio of zinc acetate to ammonium phosphite in step S2 is 1:1-1:3; After the reaction in step S2 is completed, ammonia water needs to be added dropwise to adjust the pH value to 7-9; The dispersion liquid is added in step S3 by adding the dispersion liquid to the epoxy resin at a stirring speed of 500-700 r / min and stirring for 4-6 hours; The mass ratio of the graphene oxide synergistic phosphate composite material to the epoxy resin is 1:100-1:20; the curing agent in step S3 is an aromatic amine curing agent.